Moon phases: a brief overview of Android application development in science subject - Hashim, Suhaizal; Haikal, Rosyasya; Zahir, Nur Zahira Mohamed; Zulkifli, Nurul Nadwa; Lah, Noor Hidayah Che; Firdaus, Aji Akbar (Semarak Ilmu Publishing, 2024)
Moon phases are the part of the moon shape that is directly illuminated by the sun as seen from the earth. The moon phases change gradually in about 27 days as the positions of the moon's orbit around the earth and the earth's orbit around the sun shift. The part of the moon that can be seen is from the reflection of sunlight and it depends on the position of the moon in its orbit. However, most students do not clearly understand the concept of moon phases and were unable to explain the factors that influence the occurrence of moon phases, identify changes in the shape of moon phases, sketch the order according to the sequence of moon phases and name the moon phases. As a result, the purpose of this research is to create an android application for the moon phases topic, which also serves as a medium of teaching aids for teachers and students. The foundational knowledge elements through the 3x3 Model of 21st Century Learning have been embedded through this android application. The methodology used in this study was based on design and development research (DDR) and the ASSURE instructional model has been used as a guideline in developing this android application. Respondents that were selected to evaluate the functionality of this android application through purposive sampling technic were six (6) expert evaluators within primary school science teachers and multimedia lecturers that have extensive knowledge and experience in their field of study. Besides, three students were also selected as a user to figure out their acceptance level of this android application. A checklists form was given to them to evaluate the functionality of this android application in terms of its content, interaction and interface design as the data obtained is in the form of frequency and percentage. The results of the study showed that all experts agree that the content of this android application is easy to understand, the interaction design of this android application is suitable for the student's learning needs and the interface design was animated in an interesting way that also suitable for the use by the targeted users. As such, this android application seems to be useful as one of the teaching aids for science subjects in attracting students' interest, especially in the moon phases topic and is expected to provide a positive impact in terms of functionality and usability of android application in the present and also in the future.